An unusual clinical presentation of plasma cell gingivitis related to "Acacia" containing herbal toothpaste - Anjali Makkar; Shikha Tewari; Kamal Kishor; Santprakash Kataria (Wolters Kluwer Medknow Publications, 2013)
A 17-year-old female patient presented with unusual enlargement of the gingiva with generalized alveolar bone loss. In spite of periodontal therapy, including plaque control, scaling, root planning and surgical treatment, recurrence with the same degree of the gingival enlargement and further loss of attachment level occurred. Biopsy revealed dense infiltration of normal plasma cells separated by collagenous stroma. Discontinuation of herbal toothpaste resulted in remarkable remission of the gingival enlargement within 2 weeks. Enzyme-linked immunosorbent assay of toothpaste components disclosed " Acacia" as an etiologic antigenic agent and confirmed the diagnosis of plasma cell gingivitis (PCG). Usually, PCG is not associated with the loss of attachment. This case report appears to be the first publication to document an atypical presentation of PCG with generalized aggressive periodontitis related to the use of herbal toothpaste containing " Acacia" extract from the tree "Acacia Arabica."